PEAR1, PON1, CYP2C19, CYP1A2 and F2R Polymorphisms are Associated with MACE in Clopidogrel-Treated Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Du P; Li X; Li D; Ma Y; Ni M; Li Y; Li W; Wang A; Xu X (Pharmacogenomics and Personalized Medicine)
Pengqiang Du,1 Xingang Li,2 Dandan Li,2 Yongcheng Ma,1 Ming Ni,1 Yafei Li,1 Wenbo Li,3 Aifeng Wang,1 Xiaowei Xu4 1Department of Pharmacy, Fuwai Central China Cardiovascular Hospital, Henan Provincial People’s Hospital, Central China Fuwai Hospital of Zhengzhou University, Zhengzhou, 450003, People’s Republic of China; 2Department of Pharmacy, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of China; 3Department of Cardiology, Fuwai Central China Cardiovascular Hospital, Henan Provincial People’s Hospital, Central China Fuwai Hospital of Zhengzhou University, Zhengzhou, 450003, People’s Republic of China; 4Department of Cardiology, Beijing Tiantan Hospital, Capital Medical University, Beijing, 100050, People’s Republic of ChinaCorrespondence: Aifeng Wang, Department of Pharmacy, Fuwai Central China Cardiovascular Hospital, No. 1, Fuwai Avenue, Zhengzhou, 450003, People’s Republic of China, Tel/Fax +86-371-65580160, Email waf112128@163.com Xiaowei Xu, Department of Cardiology, Beijing Tiantan Hospital, Capital Medical University, No. 119, West Nan Si Huan Road, Fengtai District, Beijing, 100070, People’s Republic of China, Email xuxiaoweittyy@sina.comObjective: The objective of this study was to evaluate the impact of clopidogrel-related gene polymorphisms on the occurrence of recurrent thrombotic events and cardiovascular death in patients with acute coronary syndrome (ACS) following percutaneous coronary intervention (PCI).Methods: We conducted genotype testing for 26 specific loci mapped to 18 clopidogrel-associated genes in ACS patients who had undergone PCI and were receiving dual antiplatelet therapy only involving clopidogrel. We documented major adverse cardiovascular events (MACE) and clinical endpoints, analyzing the effect of genetic polymorphisms on treatment outcomes.Results: A total of 200 patients were enrolled in the study, with ischemic events occurring in 21 cases. Carriers of the T-allele for rs41273215 (PEAR1), rs662 (PON1), and the A-allele for rs4244285 (CYP2C19), as well as the C-allele for rs762551 (CYP1A2), exhibited a significant increase in the risk of MACE (OR = 2.76, 95% CI = 1.46– 5.22, P = 0.002; OR = 3.72, 95% CI = 1.82– 7.64, P = 0.0003; OR = 3.86, 95% CI = 1.89– 7.86, P = 0.0002; OR = 2.40, 95% CI = 1.27– 4.55, P = 0.007). Notably, the variant T-allele of rs168753 (F2R) was associated with a significant reduction in the risk of such events (OR = 0.29, 95% CI = 0.12– 0.67, P = 0.004). No significant associations were found between other single nucleotide polymorphisms (SNPs) and clinical endpoints.Conclusion: Polymorphisms in rs41273215 (PEAR1), rs662 (PON1), rs4244285 (CYP2C19), and rs762551 (CYP1A2) were correlated with an increased risk of MACE in PCI patients. Conversely, the rs168753 (F2R) polymorphism was linked to improved cardiovascular outcomes. Genotyping for these polymorphisms could be instrumental in identifying patients at heightened risk for MACE.Keywords: clopidogrel, percutaneous coronary intervention, acute coronary syndrome, single nucleotide polymorphism, MACE